BabblePlay: An app for infants, controlled by infants, to improve early language outcomes. (May 2020) - Daffern, Helena; Keren-Portnoy, Tamar; DePaolis, Rory A.; Brown, Kenneth I.
Abstract: This project set out to develop an app for infants under one year of age that responds in real time to language-like infant utterances with attractive images on an iPad screen. Language-like vocalisations were defined as voiced utterances which were not high pitched squeals, nor shouts. The app, BabblePlay, was intended for use in psycholinguistic research to investigate the possible causal relationship between early canonical babble and early onset of word production. It is also designed for a clinical setting, (1) to illustrate the importance of feedback as a way to encourage infant vocalisations, and (2) to provide consonant production practice for infant populations that do not vocalise enough or who vocalise in an atypical way, specifically, autistic infants (once they have begun to produce consonants). This paper describes the development and testing of BabblePlay, which responds to an infant's vocalisations with colourful moving shapes on the screen that are analogous to some features of the infant's vocalization including loudness and duration. Validation testing showed high correlation between the app and two human judges in identifying vocalisations in 200 min of BabblePlay recordings, and a feasibility study conducted with 60 infants indicates that they can learn the contingency between their vocalisations and the appearance of shapes on the screen in one five minute BabblePlay session. BabblePlay meets the specification of being a simple and easy-to-use app. It has been shown to be a promising tool for research on infant language development that could lead to its use in home and professional environments to demonstrate the importance of immediate reward for vocal utterances to increase vocalisations in infants.